Terminalia chebula: An update - Chattopadhyay, R.R.; Bhattacharyya, S.K. (Pharmacognosy Reviews)
Terminalia chebula Retz. (Combretaceae) is called the “King of Medicines” in the Tibet and is always listed first in the Ayurvedic materia medica because of its extraordinary powers of healing with a wide spectrum of biological activity. The fruit of Terminalia chebula Retz. is being used for the treatment of different types of diseases and disorders since antiquity. During the last five decades, apart from the chemistry of Terminalia chebula compounds, considerable progress has been achieved regarding the biological activity and medicinal applications of Terminalia chebula. It is now considered as a valuable source of unique natural products for development of medicines against various diseases and also for the development of industrial products. This review gives a bird’s eye view mainly on the biological and pharmacological activities of Terminalia chebula extracts and some of its isolated compounds, clinical studies, plausible medicinal applications along with their safety evaluation.
Keywords: Terminalia chebula; Phytoconstituents; Biological and Pharmacological activities; Clinical studies; Medicinal uses; Safety evaluation